2021
DOI: 10.1007/s40622-020-00258-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcome of customer satisfaction: moderating effect of social trust

Abstract: The purpose of this paper is to present an integrative model of predictors and outcome of customer satisfaction in the fast food industry and also examined its effects. Moreover, we also examined the contingent effect of social trust on the relationship between customer satisfaction and brand loyalty. Both offline survey and online survey were conducted with four hundred Pakistani fast food customers; valid data were assessed and analyzed through structural equation modeling and moderation step-by-step approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 152 publications
(155 reference statements)
0
10
0
1
Order By: Relevance
“…Clean waiting areas and wards can influence the satisfaction of patients and their confidence in healthcare service. Javed et al (2021) identified cleanliness to influence patients' satisfaction in the emergency department setting. Based on these indicators, we propose that: H4a: Cleanliness positively influences patients' satisfaction with healthcare service delivery in GP clinics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clean waiting areas and wards can influence the satisfaction of patients and their confidence in healthcare service. Javed et al (2021) identified cleanliness to influence patients' satisfaction in the emergency department setting. Based on these indicators, we propose that: H4a: Cleanliness positively influences patients' satisfaction with healthcare service delivery in GP clinics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Dick and Basu [32], attitude loyalty (described as commitment, trust and satisfaction) can lead to repeated patronage intentions and thus loyal behavior. Studies [3,27,[33][34][35][36][37][38][39] have shown that relationship quality helps predict customer behaviors and plays an essential role in consumer decision making and postpurchase processes. Based on the relationship quality theory, we expanded the theory by adding variables such as value perception, tourist satisfaction, environmental commitment and environmental responsibility behavior variables to measure the pro-environmental behavior and quality perception of tourists visiting the world's largest sea beach destination.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies have recommended studying the role of top management in organizational practices as the main internal agent that mobilizes the required capabilities, resources, and support for innovations grounded on managers' perceptions (Hayton, 2005;Rao and Tilt, 2016;Al-Omoush, 2020). Furthermore, recent studies emphasize an association between CSR and social trust (Chen and Wan, 2020;Javed et al, 2021). The social trust notion describes principles, beliefs, norms, and values shared within a society as criteria used to evaluate and guide the behavior of society members and their collaborative efforts to successfully achieve social outcomes (Chen and Wan, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%